Totale Faktorproduktivität in der Bundesrepublik Deutschland: (1970-1989). Ergebnisse für das produzierende Gewerbe - Georg Erber; Alfred Haid (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
– The paper presents results for the development of total factor productivity (TFP) growth for 35 industries. It analyses the medium-term and long-term trends in these industries during the last two decades. The method used for the calculation was first proposed by Huiten (J986). It takes into account capacity utilization effects for the capital stock. Comparing the average TFP growth rates for manufacturing before, during, and after the two oil price shocks one observes that there is a steady acceleration from a fairly low 1.4per cent rate during 1970-74 to 2 per cent during 1984-89. Contrary labour productivity, measured by annual working hours, declined. Therefore the increase in TFP growth rates has to be attributed to a marked shift in capital productivity. During the early 70ies capital productivity growth rates were negative in manufacturing supporting a hypothesis of capital using and labour saving technological progress. Since then capital productivity became positive across all major subindustries in manufacturing. This led to the up-turn in TFP growth. Four hypothesis are proposed in the paper to explain the shift in the development of capital productivity growth. In the last section a number of cross-section regressions for the 35 industries for the whole period as well as a number of subperiods are calculated. As the results show Verdoorns Law seems to be valid for all periods considered Therefore high growth industries are - with respect to gross value added - leading industries in high TFP growth as well.
Keywords: D24; 330